Overcoming the Dichotomy of Knowledge and Practice: Developing a Multiple Intelligence-Based Ire Learning Model - Niken Ristianah; Fihris Kholifatul Alam (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2026)
The challenges of education in the 21st century demand a paradigm shift from centralized and monolithic learning to participatory learning that accommodates the diversity of student potential. However, the reality of Islamic Religious Education (IRE) learning in schools is often still trapped in conventional methods that only focus on developing linguistic and logical-mathematical intelligence. This article aims to conceptualize the development of an Islamic Religious Education (IRE) learning model based on Howard Gardner's theory of multiple intelligences as an alternative solution to create more holistic and meaningful learning. The method used is a literature study (library research) by analyzing various relevant sources regarding the theory of multiple intelligences, the challenges of Islamic Religious Education (IRE) learning, and the development of learning models. The results of the discussion indicate that the integration of the theory of multiple intelligences in Islamic Religious Education (IRE) learning can be done through four strategic steps: (1) identifying learning objectives, (2) analyzing teaching materials, (3) recognizing the characteristics of student intelligence, and (4) developing diverse learning methods. This model is expected to optimize students' full potential, make Islamic Religious Education (IRE) learning more enjoyable, and ultimately shape student character that aligns with Islamic values ​​holistically.